The Use of Learning Media In PAUD to Develop Children's Cognitive and Socio-Social Abilities - Erni Tresna A; Qurrotul Aeni; Tharisa Basariahna S (Feelings: Journal of Counseling and Psychology, 2024)
Early childhood is in the golden age so that cognitive and social aspects need to be improved so that the growth and development of children is optimal. The purpose of this study is to determine the type of learning media to improve children's cognitive and social aspects. This research is a descriptive qualitative research method using the library research method or literature research by reviewing written sources. The data source used is 15 journals for 5 years back. The library data collection method is carried out by reading, recording, and analyzing and then concluding the research material. The results showed that the learning process influenced the aspects of cognitive development and socio-social development of children. Media that affect the aspects of children's cognitive development on namely, dominoes, loose parts, traces media, numbers puzzles, uno cards, smart geometry boards, zoolofabets, powerpoint, and media made from natural materials. While the media that affect the aspects of children's socio-social development in the form of animated videos, hand dolls, smart roullete, and snake ladder clogs.